Brain Functional Interaction of Acupuncture Effects in Diarrhea-Dominant Irritable Bowel Syndrome - Ma, Kai; Liu, Yongkang; Shao, Wei; Sun, Jianhua; Li, Jing; Fang, Xiaokun; Li, Jing; Wang, Zhongqiu; Zhang, Daoqiang (Frontiers in Neuroscience, 2020)
Acupuncture is a traditional Chinese medicine treatment that has been widely used to modulate gastrointestinal dysfunction caused by irritable bowel syndrome (IBS) and to alleviate the resulting pain. Recent studies have shown that gastrointestinal dysfunction caused by IBS is associated with dysregulation of brain central and peripheral nervous system, while functional magnetic resonance imaging (fMRI) helps explore functional abnormality of the brain. However, previous studies rarely used fMRI to study the correlations between brain functional connection, interaction or segregation (e.g., network degree and clustering coefficient) and acupuncture stimulation in IBS. To bridge this knowledge gap, we studied the changed brain functional connection, interaction and segregation before and after acupuncture stimulation for diarrhea-dominant IBS (IBS-D) with the help of complex network methods based on fMRI. Our results indicate that the abnormal functional connections in right hippocampus, right superior occipital gyrus, left lingual gyrus,left middle occipital gyrus and cerebelum, and network degree in right middle occipital gyrus, where normal controls (NCs) are significantly different from IBS-D patients, are improved after acupuncture stimulation. The changed FCs and network degree before and after acupuncture stimulation have significant correlations with the changed clinical information including IBS symptom severity score (SSS) (r=-0.54, p=0.0085) and IBS quality of life (QOL) (r=0.426, p=0.038). We conclude that the changes of brain functional connection, interaction and segregation in hippocampus, middle and superior occipital gyrus, cerebelum and lingual gyrus may be related to acupuncture stimulation. The abnormal functional connection, interaction and segregation in IBS-D may be improved by acupuncture stimulation.